Writing and Literature Composition as Inquiry, Learning, Thinking, and Communication - Bennet, Tanya Long (Open textbook library., 2017)
In the age of Buzzfeeds, hashtags, and Tweets, students are increasingly favoring conversational writing and regarding academic writing as less pertinent in their personal lives, education, and future careers. Writing and Literature: Composition as Inquiry, Learning, Thinking and Communication connects students with works and exercises and promotes student learning that is kairotic and constructive. Dr. Tanya Long Bennett, professor of English at the University of North Georgia, poses questions that encourage active rather than passive learning. Furthering ideas presented in Contribute a Verse: A Guide to First-Year Composition as a complimentary companion, Writing and Literature builds a new conversation covering various genres of literature and writing. Students learn the various writing styles appropriate for analyzing, addressing, and critiquing these genres including poetry, novels, dramas, and research writing. The text and its pairing of helpful visual aids throughout emphasizes the importance of critical reading and analysis in producing a successful composition. Writing and Literature is a refreshing textbook that links learning, literature, and life.